On the Question of Critical Theory Today - Valantiejus, Algimantas (Sociologija. Mintis ir veiksmas, 2013)
The task of this article is to renew the discussion about the theoretical structure which includes both analytical and normative elements. The main theoretical problem analyzed in the article is the identification of analytical and normative elements in the structure of critical social theory and the analysis of the relationship between these elements in contemporary practice theories. The article seeks to answer the question why the concept of critique in contemporary practice theories is changed by the concept of reflexivity. The article aims to emphasize the implications of this „innocent“ terminological change for contemporary critical social theories, distinguished from early Critical Theory of Frankfurt School.